Origin of paleovalleys on the Rio Grande do Sul Shield (Brazil): Implications for the extent of late Paleozoic glaciation in west-central Gondwana - Fedorchuk, Nicholas D.; Isbell, John L.; Griffis, Neil P.; Montañez, Isabel P.; Vesely, Fernando F.; Iannuzzi, Roberto; Mundil, Roland; Yin, Qing-Zhu; Pauls, Kathryn N.; Rosa, Eduardo L.M. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
28 citations (Crossref) [2023-10-31]
Keywords: dept.esc; peer-reviewed

Isotopes to ice: Constraining provenance of glacial deposits and ice centers in west-central Gondwana - Griffis, Neil Patrick; Montañez, Isabel Patricia; Fedorchuk, Nicholas; Isbell, John; Mundil, Roland; Vesely, Fernando; Weinshultz, Luiz; Iannuzzi, Roberto; Gulbranson, Erik; Taboada, Arturo; Pagani, Alejandra; Sanborn, Matthew Edward; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
30 citations (Crossref) [2023-10-31]
Keywords: dept.esc; peer-reviewed

Carboniferous glaciotectonized sediments in the southernmost Paraná Basin, Brazil: Ice marginal dynamics and paleoclimate indicators - Fedorchuk, N.D.; Isbell, J.L.; Griffis, N.P.; Vesely, F.F.; Rosa, E.L.M.; Montãnez, I.P.; Mundil, R.; Yin, Q.-Z.; Iannuzzi, R.; Roesler, G.; Pauls, K.N. (Sedimentary Geology, 2019)
17 citations (Crossref) [2023-10-31]
Keywords: dept.esc; peer-reviewed

Constraining the timing, kinematics and cyclicity of Mississippian-Early Pennsylvanian glaciations in the Paraná Basin, Brazil - Rosa, Eduardo L.M.; Vesely, Fernando F.; Isbell, John L.; Kipper, Felipe; Fedorchuk, Nicholas D.; Souza, Paulo A. (Sedimentary Geology, 2019)
32 citations (Crossref) [2023-10-31]
Keywords: dept.esc; peer-reviewed

Fossil subduction zone origin for magmas in the Ferrar Large Igneous Province, Antarctica: Evidence from PGE and Os isotope systematics in the Basement Sill of the McMurdo Dry Valleys - Choi, Sung Hi; Mukasa, Samuel B.; Ravizza, Greg; Fleming, Thomas H.; Marsh, Bruce D.; Bédard, Jean H.J. (Earth and Planetary Science Letters, 2019)
Mantle plumes provide an attractive mechanism for generating short-duration, voluminous magmas in large igneous provinces (LIPs) while at the same time providing an explanation for the frequently associated break-up of supercontinents. This model has also been invoked for the Ferrar large igneous province (FLIP) in Antarctica, which zircon and baddeleyite U–Pb dating shows was emplaced over a short duration at 182.7 ± 0.5 Ma, contemporaneously with fragmentation of the supercontinent Gondwanaland. Here, we present platinum-group-element (PGE) and Os-isotopic data for the Basement Sill in the McMurdo Dry Valleys – a part of the FLIP – that challenge the plume interpretation. The Basement Sill samples studied are cumulate-textured gabbro to norite, and pyroxenite with minor ferro- or leuco-lithofacies with MgO ranging from 2 to 19 wt%. The 187Os/188Os values range from 0.1609 ± 0.003 (2σ) to 8.100 ± 1.600 (2σ); the minimum value overlaps with a previously published estimated initial 187Os/188Os ratio for Ferrar magmas of 0.145 ± 0.049 (2σ). The PGE abundance patterns for the Basement Sill define positive, convex-shaped slopes between the IPGE (Os, Ir and Ru) and PPGE (Pt, Pd and Rh). The most significant feature of the entire data set is the extreme sub-chondritic Os/Ir ratios (<0.33), values which are atypical of plume-derived magmas. These low Os/Ir ratios are more consistent with the alternative view that FLIP resulted from the decompression melting of mantle with a fossil subduction zone signature along the proto-Pacific margin of Gondwanaland, disaggregated by rifting related to plate rearrangements during supercontinent break-up. We propose that hydrated fossil subduction zones elsewhere on Earth might account for other short-lived voluminous magmatic events that form LIPs. The remarkably short duration of these events may be due to rapid decompression of hydrated mantle allowing instantaneous large-volume melting which then peters out quickly (<1 Myr) as H2O is expelled from the source rocks and into the melt. © 2018 Elsevier B.V.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/120-491-356-625-301, pop00064 tex.type: [object Object]
Keywords: Antarctica; Basement Sill; Buildings; Decompression melting; East Antarctica; Ferrar LIP; Hydration; Isotopes; Large Igneous Provinces (LIPs); Large igneous provinces; Magnesia; McMurdo Dry Valleys; Melting; PGE; Platinum group elements; Silicate minerals; Subduction zones; Zircon; basement rock; dept.esc; fossil; fossil subduction zone; isotopic analysis; large igneous province; magma; mantle plume; osmium isotope; peer-reviewed; platinum group element; sill; subduction zone